HAKIM PENGAWAS DAN PENGAMAT : PENJAGA HAK-HAK NARAPIDANA - Petrus Irwan Panjaitan (GEVANGENEN Jurnal Pemasyarakatan, 2025)
Indonesia is a state based on the rule of law that recognizes and respects human rights as the rights of every citizen. The recognition of these fundamental rights also applies to individuals who have been sentenced to imprisonment by a court decision. Even as convicts, their rights remain acknowledged as stipulated in Law of the Republic of Indonesia No. 2 of 2022 concerning Corrections. The various rights inherent to inmates during the correctional process must not be neglected or violated. To safeguard the rights of prisoners while serving their sentences or undergoing the correctional process within correctional institutions, the state, through legislation specifically Law of the Republic of Indonesia No. 8 of 1981 on the Criminal Procedure Code, Articles 277 to 283, as well as Supreme Court Circular No. 7 of 1985 concerning Guidelines for the Duties of Judges and Supervising Judges ensures such protection. Therefore, judges serve as the guardians of prisoners’ rights.